The Sense in Image: the Communication of Contemporary Strategies of facing the World through the Picture - Ana Taís Martins Portanova Barros (Galáxia, 2010)
This work verifies to what extent the picture, product of a mediation strongly technique, can reveal an imaginary. With the presupposition that the pictures constitute communicative actions to share world visions, we examined phtographs done by amateurs. The aim is to use the Studies of the Imaginary by Gilbert Durand to look symbolic images for the photographic images. It is ended that the symbolic imagination is present also in an activity eminently technique as the picture, and that the abundance of pictures of the intimate banalities indicates a conversion of the objetictiv and warlike imaginary to an euphemistic and subjetctiv imaginary.